Safety Evaluation of Burdock (Arctium Lappa L.) Root Extract: Effects on Spleen Histopathology and Peripheral Lymphocytes in Wistar Rats - Faizal, Imam Agus; Afrilla, Rananda; Farabi, Meka Faizal; Savitri, Lisa (Poltekkes Kemenkes Semarang, 2025)
Arctium lappa L. (burdock) root contains phytochemicals—including flavonoids, saponins, and phenolic compounds—reported to exhibit immunomodulatory activity. This study evaluated the safety of Arctium lappa L. root extract through a 28-day post-test experimental design involving male and female Wistar rats. Eight animals were randomized into four groups receiving oral doses of 0, 150, 300, or 450 mg/kg BW/day. Lymphocyte counts were measured using an automated analyzer, and splenic histopathology was assessed on Hematoxylin–Eosin–stained sections using semiquantitative scoring. Lymphocyte values (mean ± SD) showed no significant differences among groups (p > 0.05; small effect size) and remained within physiological limits, with males ranging from 4.14 ± 0.21 to 7.96 ± 0.34 ×10³/µL and females from 2.04 ± 0.18 to 15.43 ± 0.52 ×10³/µL. No necrotic lesions were identified in any dose group. Splenic congestion and extramedullary hematopoiesis were mild to moderate, remaining below 30–50% involvement without architectural disruption. These findings indicated that repeated oral exposure to A. lappa extract up to 450 mg/kg BW/day did not induce structural injury or suppress immune-cell profiles, supporting its preliminary safety for further toxicological and immunopharmacological investigation.